Relationship between Foreign Direct Investment and Company Taxation: Case of Bangladesh - Ahmed, Alim Al Ayub (American Journal of Trade and Policy, 2016)
This study looks at the association between foreign direct investment and company taxation in Bangladesh from 2001-2010. The annual reports were sourced from the Bangladesh Bank Bulletin, Bangladesh Bureau of Statistics (BBS) and World Bank which was analyzed using Descriptive Statistic, correlation and regression. The independent variable corporate taxation was measured using corporate tax rate (CTR) whilst dependent variable foreign direct investment was measured using FDI net inflow (% of GDP). GDP, exchange rate and inflation rate were used as control variables. The result showed negative significant relationship between CTR and FDI whereas exchange rate and FDI indicated negative insignificant relationship. On the other hand, GDP was positively insignificantly related with FDI whilst inflation had positive significant relationship with FDI. Based on the result, the study suggested that there is require for the government to lo trim down corporate tax rate in order to create a centre of attention FDI into the country.
Keywords: Company Taxation; Corporate Tax Rate; Foreign Direct Investment (FDI); GDP; Bangladesh